PROFITABILITAS SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN PADA AUDIT REPORT LAG - Pratiwi, Ni Luh Made Winda; Sari, Maria M Ratna (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This research aims to study profitability as the moderator for the impact of company size on audit report lag. The population used in this research is manufacturing companies listed on the Stock Exchange in 2012-2014 as many as 432 companies. Determination of the sample using purposive sampling technique with a sample of 300 observation. . The analysis technique used is Moderated Regression Analysis (MRA). The analysis results show that the size of a company has negative impact on audit report lag and profitability weakens the impact of a company size on audit report lag. The influence of the independent variable on the dependent variable is equal to 5.4 percent and the remaining 94.6 percent is influenced by other variables outside the model.
Keywords: Audit Report Lag; Firm Size; Profitability